(untitled) (Journal of Ideas in Health, 2023)
Background: Botox, derived from the toxin produced by Clostridium botulinum, is an attenuated toxin employed as a treatment for cervical dystonia, overactive bladder, strabismus, cerebral palsy, and non-surgical cosmetic procedures. This study aimed to explore the impact of injecting Botox around the facial nerve on the left side of rabbits, specifically focusing on the histological changes in the zygomatic bone. Methods: Twenty-five adult rabbits of a local breed, weighing 1500-1800 gm and of both sexes, underwent a 15-day acclimation period prior to the experiment. The rabbits were randomly assigned to four groups (1st, 2nd, 3rd, and 4th). A singular intramuscular injection of Botox at a dose of 3.5 U/kg was administered to the left facial muscles. The rabbits in each group were then sacrificed at distinct time points after injection: day 10, day 15, day 30, and day 45. All rabbits survived until the end of the experiment, at which point they were euthanized with chloroform. Post-euthanasia, the rabbits’ facial zygomatic bones were dissected and subjected to histological assessment. Results: The results indicated notable changes in the zygomatic bone, including prominent vacuoles within the bony matrix, cracks with cellular debris, limited osteocytes, and collagen bundles resembling woven bone. Additionally, in the day 30 group (T3), irregular bone borders and atrophied osteogenic cells were observed, while the day 45 group (T4) exhibited necrotic areas and bone fragments within the bone matrix. Conclusion: In conclusion, Botox, derived from Clostridium botulinum, serves various medical purposes. The study focused on injecting Botox around rabbits’ facial nerves to assess its impact on zygomatic bones histologically. Following a controlled injection and specific time intervals, the examined bone samples exhibited distinct changes, providing insights into Botox’s effects on bone morphology.